2017
DOI: 10.1002/lary.26949
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus Aureus V8 protease disrupts the integrity of the airway epithelial barrier and impairs IL‐6 production in vitro

Abstract: Objective: Staphylococcus aureus (S. aureus) infection is known to contribute to the severity and recalcitrance of chronic rhinosinusitis (CRS), and its secreted products have been shown to alter the airway barrier. Extracellular proteases secreted by S. aureus are thought to be important in epithelial infection and immune evasion; however, their effect on airway mucosal barrier function is not known.Methods: To investigate the impact of extracellular proteases on airway epithelial integrity, the purified S. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 49 publications
2
29
0
Order By: Relevance
“…Tight junctions are involved in the regulation of solute and ion transport across epithelia and are localised at the apicolateral border of individual airway epithelial cells 3 , 5 , 60 . Certain bacterial 41 , 61 , 62 and viral 42 , 63 pathogens specifically target and degrade the tight junctions of airway epithelia during paracellular infection processes. Therefore, the presence of normal, functioning tight junctions is an essential feature of differentiated AECs to allow for representative modelling of respiratory tract infections.…”
Section: Discussionmentioning
confidence: 99%
“…Tight junctions are involved in the regulation of solute and ion transport across epithelia and are localised at the apicolateral border of individual airway epithelial cells 3 , 5 , 60 . Certain bacterial 41 , 61 , 62 and viral 42 , 63 pathogens specifically target and degrade the tight junctions of airway epithelia during paracellular infection processes. Therefore, the presence of normal, functioning tight junctions is an essential feature of differentiated AECs to allow for representative modelling of respiratory tract infections.…”
Section: Discussionmentioning
confidence: 99%
“…SspA is produced upon S. aureus phagocytosis by neutrophils, suggesting its role in facilitating S. aureus intracellular escape, potentially through activating the cysteine protease, Staphopain B (254). SspA can disrupt epithelial barriers, compromising cell junction integrity (265,268). Skin infection models of sspA mutants suggest a slight decrease in bacterial fitness in vivo (269).…”
Section: B) Enzymes That Degrade Host Tissue Componentsmentioning
confidence: 99%
“…It is frequently found in severe chronic inflammatory diseases of the gut, skin, and airway such as inflammatory bowel disease, allergic dermatitis, and asthma (Weidinger et al, 2008; Turner, 2009). In the context of CRS, bacterial secreted products as well as different cytokines have been reported to disrupt the mucosal barrier in vitro , and barrier dysfunction has been proposed to have a critical role in the pathogenesis of this disease (Tieu et al, 2009; Soyka et al, 2012; Malik et al, 2015; Ramezanpour et al, 2016; Murphy et al, 2017). Results of previous studies with primary alveolar pneumocytes indicated that P. aeruginosa elastase enhanced epithelial permeability by redistribution and disruption of tight junction proteins (Azghani et al, 2000).…”
Section: Discussionmentioning
confidence: 99%